Understanding the Global Energy Crisis - Coyle, Eugene D. (Purdue University Press, 2014)
Central issues in global energy are discussed through interdisciplinary dialogue between experts from both North America and Europe with overview from historical, political, and socio-cultural perspectives, outlining the technology and policy issues facing the development of major conventional and renewable energy sources. We are facing a global energy crisis caused by world population growth, an escalating increase in demand, and continued dependence on fossil-based fuels for generation. It is widely accepted that increases in greenhouse gas concentration levels, if not reversed, will result in major changes to world climate with consequential effects on our society and economy. This is just the kind of intractable problem that Purdue University's Global Policy Research Institute seeks to address in the Purdue Studies in Public Policy series by promoting the engagement between policy makers and experts in fields such as engineering and technology.